Closed circuit television: towards an aesthetics of monitoring and surveillance - Arçari, André (Farol, 2024)
The essay aims to analyze the constitution of images generated by Closed-Circuit Television (CCTV) as elements of videoart, starting from its beginnings in the 1970s. It examines works such as Live-Taped Video Corridor (1970) and Four Corner Piece (1971) by Bruce Nauman, as well as Observation of observation: indeterminacy (1973) by Peter Weibel. The focus is on understanding the process of image formation by these devices and their implications as real/virtual blocking mechanisms related to insecurity and fear, within the context of a well-established industry we supposed to exist, that is socially and culturally constructed. In dialogue with the artists, the essay draws on the dialogue with a text about video and narcissism (1976) by Rosalind Krauss and the theoretical concepts of disciplinary society by Michel Foucault and control society by Gilles Deleuze, in order to explore this apparatus that generates images in the art field, which diverges from its conventional use in public and private spaces as a tool for protection and security.